2021
DOI: 10.1021/acs.jmedchem.1c00596
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 1-Benzoyl 4-Phenoxypiperidines as Small-Molecule Inhibitors of the β-Catenin/B-Cell Lymphoma 9 Protein–Protein Interaction

Abstract: Structure-based design and optimization were performed to develop small-molecule β-catenin/B-cell lymphoma 9 (BCL9) inhibitors and improve their inhibitory activities. Compound ZL3138 with a novel 1-benzoyl 4-phenoxypiperidine scaffold was discovered to disrupt the β-catenin/BCL9 protein–protein interaction (PPI) with a K i of 0.96 μM in AlphaScreen competitive inhibition assays and displayed good selectivity for β-catenin/BCL9 over β-catenin/E-cadherin PPIs. The binding mode of new inhibitors was characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…Although there have been reports of using small molecule and peptide inhibitors to block the b-catenin-BCL9 interaction, there are few examples of unnatural peptidomimetic inhibitors. [48][49][50][51][52][53][54][55][56][57] It is still a big challenge to design effective peptidomimetic inhibitors to enter cells and block the b-catenin-BCL9 interaction.…”
Section: Inhibitors Of Bcl9-b-catenin Ppismentioning
confidence: 99%
“…Although there have been reports of using small molecule and peptide inhibitors to block the b-catenin-BCL9 interaction, there are few examples of unnatural peptidomimetic inhibitors. [48][49][50][51][52][53][54][55][56][57] It is still a big challenge to design effective peptidomimetic inhibitors to enter cells and block the b-catenin-BCL9 interaction.…”
Section: Inhibitors Of Bcl9-b-catenin Ppismentioning
confidence: 99%
“…Co-immunoprecipitation (co-IP) can investigate endogenous interactions between two proteins in intact cells and uses a bait-specific antibody to precipitate the bait protein as well as binding partners, which are then detected by MS or Western blotting . Li et al used a co-IP assay to evaluate the effect and selectivity of inhibitors on the β-catenin and BCL9 association in HCT116 cells with hyperactive β-catenin signaling . However, co-IP may not detect low-affinity interactions and transient PPIs.…”
Section: Assays For Evaluating β-Catenin and Its Nuclear Partner Ppi ...mentioning
confidence: 99%
“…With recent development in pharmaceuticals, various novel drugs targeting PPIs are currently in the pre-clinical and clinical stages. For example, 1-benzoyl 4-phenoxypiperidines, a small molecular inhibitor, blocks the PPIs between β-catenin and B-cell lymphoma 9 ( Li et al, 2021 ). A previous study has shown that the PPIs between B-cell lymphoma-2 and Parkin mediate mitophagy via the PTEN-induced putative kinase 1/Parkin pathway in the lipopolysaccharide-induced lung injury ( Zhang Z et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%